The Effect of Freight and Passenger Transportation and Energy Production on Economic Growth in the Framework of Macro-Economic Indicators: The Case of Kazakhstan - Dyussembekova, Zhanar; Aidarova, Aina B.; Balapanova, Elmira; Kuatova, Dilmina; Seitkhamzina, Gaukhar Zh.; Bolganbayev, Artur (International Journal of Energy Economics and Policy, 2023)
This study analyzes the impact of freight and passenger transport and energy production on the economic growth of Kazakhstan in the period 1996-2021 using the VAR model. The analysis also includes control variables such as energy production, economic growth, exchange rates, inflation, interest rates, foreign direct investment, and unemployment. The research uses data from the World Bank, the Central Bank of Kazakhstan, and the National Bureau of Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan. The findings showed that freight transportation’s current and one-term lagged value affects economic growth. After determining the significance of the effect, we examined its causality. The findings concluded that none of the independent variables had a causal effect on economic growth, whereas the model with all three independent variables has. The study chose a long study interval and determined the data frequency as annual. The data period may be chosen as monthly or quarterly, and the effects of fluctuations during the year may be examined separately. As the timeline graph shows, the Covid-19 period created a significant statistical disruption for passenger transport. Future researchers may analyze this effect using the series from the pandemic period.